2023
DOI: 10.3390/foods12152834
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sheep Tail Fat, Fat Level, and Cooking Time on the Formation of Nε-(carboxymethyl)lysine and Volatile Compounds in Beef Meatballs

Abstract: This study aimed to determine the effects of fat type (sheep tail fat (STF) and beef fat (BF)), fat levels (10, 20, or 30%), and cooking time (0, 2, 4, and 6 min, dry heat cooking at 180 °C) on the carboxymethyl lysine (CML) content in meatballs. pH, thiobarbituric acid reactive substance (TBARS), and volatile compound analyses were also performed on the samples. The use of STF and the fat level had no significant effect on the pH value. The highest TBARS value was observed with the combination of a 30% fat le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Other studies have also shown that CML reflects heat treatment intensity (Chen & Smith, 2015 ; Öztürk et al., 2023 ; Sun et al., 2015 ; Trevisan et al., 2016 ; Zhu, Fang, et al., 2020 ; Zhu, Huang, et al., 2020 ). The formation of CML is influenced by factors such as meat type, fat type, and ingredients (Chen & Smith, 2015 ; Öztürk et al., 2023 ; Zhu, Fang, et al.,  2020 ; Zhu, Huang, et al., 2020 ). In the current study, using STF had no influence on TBARS, total sulfhydryl, carbonyl contents, or CML content (Table 2 ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Other studies have also shown that CML reflects heat treatment intensity (Chen & Smith, 2015 ; Öztürk et al., 2023 ; Sun et al., 2015 ; Trevisan et al., 2016 ; Zhu, Fang, et al., 2020 ; Zhu, Huang, et al., 2020 ). The formation of CML is influenced by factors such as meat type, fat type, and ingredients (Chen & Smith, 2015 ; Öztürk et al., 2023 ; Zhu, Fang, et al.,  2020 ; Zhu, Huang, et al., 2020 ). In the current study, using STF had no influence on TBARS, total sulfhydryl, carbonyl contents, or CML content (Table 2 ).…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, it was reported that STF increased CML content in meatballs cooked at 180°C (dry heating), and this result was associated with the TBARS value. Furthermore, it was emphasized that STF is more effective in CML formation as cooking time increases (Öztürk et al., 2023 ). In the present study, cooking time had a very significant effect on CML content ( p < .01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation